Water Table Fluctuation and Methane Emission in Pineapples (Ananas comosus (L.) Merr.) Cultivated on a Tropical Peatland - Wendy Luta; Osumanu Haruna Ahmed; Latifah Omar; Roland Kueh Jui Heng; Liza Nuriati Lim Kim Choo; Mohamadu Boyie Jalloh; Adiza Alhassan Musah; Arifin Abdu (MDPI AG, 2021)
Inappropriate drainage and agricultural development on tropical peatland may lead to an increase in methane (CH₄) emission, thus expediting the rate of global warming and climate change. It was hypothesized that water table fluctuation affects CH₄ emission in pineapple cultivation on tropical peat soils. The objectives of this study were to: (i) quantify CH₄ emission from a tropical peat soil cultivated with pineapple and (ii) determine the effects of water table depth on CH₄ emission from a peat soil under simulated water table fluctuation. Soil CH₄ emissions from an open field pineapple cultivation system and field lysimeters were determined using the closed chamber method. High-density polyethylene field lysimeters were set up to simulate the natural condition of cultivated drained peat soils under different water table fluctuations. The soil CH₄ flux was measured at five-time intervals to obtain a 24 h CH₄ emission in the dry and wet seasons during low- and high-water tables. Soil CH₄ emissions from open field pineapple cultivation were significantly lower compared with field lysimeters under simulated water table fluctuation. Soil CH₄ emissions throughout the dry and wet seasons irrespective of water table fluctuation were not affected by soil temperature but emissions were influenced by the balance between methanogenic and methanotrophic microorganisms controlling CH₄ production and consumption, CH₄ transportation through molecular diffusion via peat pore spaces, and non-microbial CH₄ production in peat soils. Findings from the study suggest that water table fluctuation at the soil–water interface relatively controls the soil CH₄ emission from lysimeters under simulated low- and high-water table fluctuation. The findings of this study provide an understanding of the effects of water table fluctuation on CH₄ emission in a tropical peatland cultivated with pineapple.